The plasma lipid peroxidation intensity (MDA) and chain-breaking antioxidant concentrations in the cows with clinic or subclinic mastitis - Kizil, O.; Akar, Y.; Saat, N.; Kizil, M.; Yukseu, M. (Ecole Nationale Veterinaire Toulouse, 2007)
The aim of this study was to determine lipid peroxidation intensity by measurement of plasma malonedialdehyde (MDA) concentrations and plasma chain-breaking antioxidant concentrations such as reduced glutathione (GSH), vitamin A, E, C and beta-carotene in the cows with and without mastitis. The study was conducted on 30 Holstein cows which were divided into 3 equal groups on the basis of clinical examination and California Mastitis Test (CMT): in the group CM, clinical mastitis was evidenced; in the group SCM, mastitis was subclinical, and the group C served as a control. The plasma lipid peroxidation index was measured according to the concentration of thiobarbituric acid reactive species (MDA), and GSH activity was measured spectrophotometrically using Ellman's reagent. Vitamin A, P-carotene and vitamin E values were spectrophotometrically determined, and vitamin C value was colorimetrically determined using a phosphotungstic acid method. The mean plasma GSH (p<0.01) and beta-carotene (p<0.001) concentrations were showed significant differences between the 3 groups, whereas mean plasma MDA and serum vitamin C concentrations significantly differed only between the C and CM groups (p<0.05). The decreased chain-breaking antioxidant concentrations and the enhanced concentrations of GSH and MDA suggest that an inflammatory-related oxidative stress occurs in the cows with clinical and subclinical mastitis.
Keywords: vitamin C; vitamin A; vitamin E; beta-carotene; glutathion; lipid peroxidation; cow; mastitis